Peningkatan Hasil Belajar Tematik menggunakan Model Discovery Learning di Kelas SD - Efrina, Ressy; Lena, Mai Sri (Universitas Negeri Padang, 2022)
This study aims to explain the learning outcomes of students using the Discovery Learning model in thematic learning in class IV SD 13 Seberang, North Padang. This research is a class action that uses qualitative and quantitative approaches. The subjects of this study were the teacher as the observer, the researcher as a practitioner, and the fourth grade students of SDN 13 Seberang, North Padang, amounting to 21 people. The results of this study are: (1) The percentage of RPP observations has increased from 79% to 95% in each cycle. (2) The teacher aspect in the first cycle was 81.25%, increasing to 93.75% in the second cycle. (3) The aspect of students experienced an increase in percentage from 81.25% to 93.75%. (4) Student learning outcomes, in the first cycle the percentage value of 71.4% with category C to 95.2% in the SB category in the second cycle.